2017
DOI: 10.1021/acs.analchem.6b04897
|View full text |Cite
|
Sign up to set email alerts
|

Small Emitter Tips for Native Mass Spectrometry of Proteins and Protein Complexes from Nonvolatile Buffers That Mimic the Intracellular Environment

Abstract: Salts are often necessary to maintain the native structures and functions of many proteins and protein complexes, but many buffers adversely affect protein analysis by native mass spectrometry (MS). Here, protein and protein complex ions are formed directly from a 150 mM KCl and 25 mM Tris-HCl buffer at pH 7 that is widely used in protein chemistry to mimic the intracellular environment. The protein charge-state distributions are not resolved from electrospray ionization MS using 1.6 μm diameter emitter tips, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
174
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(180 citation statements)
references
References 58 publications
5
174
1
Order By: Relevance
“…We recently proposed that this desalting phenomenon with small emitter tips occurs when initial droplets are small enough to contain on average fewer than one protein molecule,s uch that small droplets that contain ap rotein molecule have al ower ratio of salt to protein than larger droplets that contain on average multiple protein molecules. [20] Them uch larger salt cluster ions observed with the larger tips than with the smaller tips (for example,F igure 2e vs.2 j) is consistent with this mechanism. Thec harge-state distributions of the protein and protein complexes from all six buffers with the submicrometer emitter tips are nearly identical to those from aqueous ammonium acetate with the larger emitter tips,indicating that any effects of acidification and proton-enrichment of the smaller droplets [18] are negligible.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…We recently proposed that this desalting phenomenon with small emitter tips occurs when initial droplets are small enough to contain on average fewer than one protein molecule,s uch that small droplets that contain ap rotein molecule have al ower ratio of salt to protein than larger droplets that contain on average multiple protein molecules. [20] Them uch larger salt cluster ions observed with the larger tips than with the smaller tips (for example,F igure 2e vs.2 j) is consistent with this mechanism. Thec harge-state distributions of the protein and protein complexes from all six buffers with the submicrometer emitter tips are nearly identical to those from aqueous ammonium acetate with the larger emitter tips,indicating that any effects of acidification and proton-enrichment of the smaller droplets [18] are negligible.…”
supporting
confidence: 58%
“…[7,8,[13][14][15][16][17] Nanoelectrospray (nano-ESI) emitters with tip diameters of about 1 mmor smaller produce ions that have less sodium ion adduction than do those formed using larger tips. [18][19][20] This method has been demonstrated for solutions containing organic solvents and acid in which proteins are denatured and from aqueous solutions with up to 25 mm NaCl. [18,19] It has been proposed that the droplets from the smaller emitter tips undergo more solvent acidification and less solvent evaporation and fission events than larger droplets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The submicron emitters were chosen to help reduce salt adducts on the protein ions and to reduce the chemical noise (Susa et al, 2017). Nanoelectrospray ionization was initiated by applying a voltage of ~1.0 kV to 1.2 kV onto a platinum wire (0.127 mm in diameter, Sigma, St. Louis, MO, USA) that is inserted inside the emitter and in contact with sample solutions.…”
Section: Electrospray Ionization Mass Spectrometrymentioning
confidence: 99%
“…More recently it has been shown that using submicrometer nano-ESI capillaries (<0.5 mm compared with conventional emitter sizes of 1-10 lm) enable the detection of well-resolved charge state distributions for native proteins and protein complexes analyzed from highsalt biochemical buffers (e.g. 25 mM Tris-HCl, 150 mM NaCl and phosphate buffered saline) [71,72]. This technology has also been demonstrated to be applicable for the analysis of detergent solubilized MPs by nano-ESI (in 150 mM NaCl, 25 mM Tris-HCl, 1.1% (w/v) n-octyl-b-D-glucoside) [73].…”
Section: Introductionmentioning
confidence: 99%